Analisis Pengaruh Kepemimpinan, Disiplin, dan Motivasi Kerja Terhadap Kinerja Karyawan CV. Kilos Barasiah Sadayana Ciputat - Purwanti Purwanti (CV. Syntax Corporation Indonesia, 2022)
The obstacle that often occurs is when the delivery schedule is delayed, in these circumstances it needs good work discipline, so that it can be followed up as soon as possible so as not to cause disappointment from consumers This research aims to describe the problems that exist in the CV. Kilos Barasiah Sadayana where the development of the business sector needs basic household needs (Laundry) opportunities for small companies for sub-sectoral jobs. Take advantage of opportunities to reach consumers, creating competition between similar repair service companies. This also makes every company must innovate a creative marketing strategy in selling goods offered to the target target. The type of research used in this writing is descriptive research, using a qualitative approach. The results obtained, namely CV. Kilos Barasiah Sadayana is a small business in the field of household (Laundry) in Ciputat south tangerang. This small and medium-sized business (MSME) conducts good leadership with employees, employee motivation with the form of rewards to its employees. Moreover, also a good level of dyspline which is very minimal complaints from consumers